The Association Between Neighborhood Poverty and Hippocampal Volume Among Individuals at Clinical High-Risk for Psychosis: The Moderating Role of Social Engagement. (11th June 2022) - Ku, Benson S; Aberizk, Katrina; Addington, Jean; Bearden, Carrie E; Cadenhead, Kristin S; Cannon, Tyrone D; Carrión, Ricardo E; Compton, Michael T; Cornblatt, Barbara A; Druss, Benjamin G; Mathalon, Daniel H; Perkins, Diana O; et al.
Abstract: Reductions in hippocampal volume (HV) have been associated with both prolonged exposure to stress and psychotic illness. This study sought to determine whether higher levels of neighborhood poverty would be associated with reduced HV among individuals at clinical high-risk for psychosis (CHR-P), and whether social engagement would moderate this association. This cross-sectional study included a sample of participants ( N   =  174, age-range = 12–33 years, 35.1% female) recruited for the second phase of the North American Prodrome Longitudinal Study. Generalized linear mixed models tested the association between neighborhood poverty and bilateral HV, as well as the moderating role of social engagement on this association. Higher levels of neighborhood poverty were associated with reduced left (β  =  −0.180, P  =  .016) and right HV (β  =  −0.185, P  =  .016). Social engagement significantly moderated the relation between neighborhood poverty and bilateral HV. In participants with lower levels of social engagement ( n   =  77), neighborhood poverty was associated with reduced left (β  =  −0.266, P  =  .006) and right HV (β = −0.316, P  = .002). Among participants with higher levels of social engagement ( n  = 97), neighborhood poverty was not significantly associated with left (β  =  −0.010, P  =  .932) or right HV (β  =  0.087, P  =  .473). In this study, social engagement moderated the inverse relation between neighborhood poverty and HV. These findings demonstrate the importance of including broader environmental influences and indices of social engagement when conceptualizing adversity and potential interventions for individuals at CHR-P.